Synchronization of Labor Protection Norms Through a Reasonable Accommodation Approach - Arika Rachmah; Taletha Audrey Az Zahraqeela Novangelista; Nasywa Khalisa Putri Pinilihan; Moosa Sheikh; Widya Daniswara (Disable, 2026)
In Indonesia, the employment rate of the deaf community is still low, with most working in the informal sector. This is despite their constitutional rights and the country's commitment to the Convention on the Rights of Persons with Disabilities (CRPD). This situation highlights the difference between the legal recognition of labor rights and their actual application. This study examines the legal framework governing the factors contributing to the failure of labor market integration from normative, structural, and implementation perspectives, as well as the rights and obligations of deaf workers from a comparative legal perspective, and formulates an inclusive, rights-based regulatory model. A normative legal approach with prescriptive analysis, vertical-horizontal regulatory synchronization, and a comparative study with the UK’s Equality Act 2010 and the principle of reasonable accommodation were employed in this study. The results show that the quota-based approach in Indonesia is constrained by unclear technical accommodations, weak sanctions, and regulatory inconsistencies, resulting in work inclusion that is largely formalistic with low compliance rates. The failure to achieve employment targets is attributed to misinterpretations of the “physically healthy” requirement, structural weaknesses regarding the financing of assistive technology, and implementation practices that rely on corporate interpretation. This study recommends the establishment of a Disability Employment Fund, the integration of the principle of reasonable accommodation, and the strengthening of the role of the Disability Committee to ensure sustainable access to employment and shift the perception of disability from a cost burden to a productive asset.